Efektivitas Model Pembelajaran Guided Discovery Learning terhadap Hasil Belajar Matematika - Witri Lestari (Universitas Indraprasta PGRI Jakarta, 2017)
This research is aimed at showing the effectiveness of the use of a guided discovery learning model on mathematical learning outcomes at a cognitive domain. The research method used is a quasi-experiment with research design of non-equivalent control grup. The research takes 46 samples, consisting of 23 samples for experimental class and 23 samples for control class. The sampling technique used is a nonrandom technique. The type of instrument distributed is a test in the form of 10 essay questions. The result of the research test shows that ????1 is accepted, meaning there is a difference between the average learning outcomes of mathematics postest of students taught employing guided discovery learning model and those of students taught applying a varied lecture learning method. In conclusion, the guided discovery learning model affects learning outcomes and is effective to be used as a learning model in geometry subject.